Cultural Diversity: Obstacle or Help in Building European Unity? - Petr Pit'ha (Universidad de Navarra, 2009)
The cultural problems of a united Europe are discussed and the difference between the genesis of US and EU are described. Positive aspeccts of the multicultural character of Europe are shown, and it is discussed how to use them. The dangers of surface syncretism are opposed with the cultivation of local cultures. Formal tolerance is then shown as vulnerable in comparison with mutual understanding based on an underlying sameness of the variety of European cultures. Language differences are used as a main illustration in the whole argumentation. Finally, it is claimed that the education for democracy should be anchored in much better education of the first and other languages as well as in the profound knowledge of local culture